PARADIGMA TAFSIR DAKWAH: PENDEKATAN KONSELING - Ahmad Rifai (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2018)
Tafsir dakwah is an effort to understand the meaning of Qur’an verses by using dakwah thinking as analysis knife. The good methodology that good to be followed in discussing Tafsir dakwah is thematic method (Maudu’i). By this thematic method, hoped Mufasir will get comprehensive illustration from the Qur’an about dakwah problem that is proposed to him.